Does Cognitive Impairment Affect Rehabilitation Outcome in Parkinson’s Disease? - Ferrazzoli, Davide; Ortelli, Paola; Maestri, Roberto; Bera, Rossana; Giladi, Nir; Ghilardi, Maria Felice; Pezzoli, Gianni; Frazzitta, Giuseppe (Frontiers in Aging Neuroscience, 2016)
Background: The cognitive status is generally considered as a major determinant of rehabilitation outcome in Parkinson’s disease. No studies about the effect of cognitive impairment on motor rehabilitation outcomes in Parkinson’s disease have been performed before. Objective: This study is aimed to evaluate the impact of cognitive decline on rehabilitation outcomes in patients with Parkinson’s disease. Methods: We retrospectively identified 485 patients with Parkinson’s disease hospitalized for a 4-week Multidisciplinary Intensive Rehabilitation Treatment between January 2014 and September 2015. According to Mini Mental State Examination (MMSE), patients were divided into: group 1 - normal cognition (score 27-30), group 2 - mild cognitive impairment (score 21-26), group 3 - moderate or severe cognitive impairment (score ≤ 20). According to Frontal Assessment Battery (FAB), subjects were divided into patients with normal (score ≥ 13.8) and pathological (score < 13.8) executive functions. The outcomes measures were: Unified Parkinson’s Disease Rating Scale, Parkinson’s Disease Disability Scale, Six Minutes Walking, Timed Up and Go Test and Berg Balance Scale. Results: All scales had worse values with the increasing of cognitive impairment and passing from normal to pathological executive functions. After rehabilitation, all the outcome measures improved in all groups (p<0.0001). Between groups, the percentage of improvement was significantly different for total UPDRS (p=0.0009, best improvement in normal MMSE group; p=0.019, best improvement in normal FAB group), and Berg Balance Scale (p<0.0001, all pairwise comparisons significant, best improvement in patients with worse MMSE score; p<0.0001, best improvement in patients with pathological FAB). Timed Up and Go Test (p=0.006) and Berg Balance Scale (p<0.0001) improved in patients with pathological FAB score, more than in those with normal FAB score. Conclusions: Patients gain benefit in the rehabilitative outcomes, regardless of cognition. Our data suggest that rehabilitation could be effective also in Parkinsonian subjects with cognitive impairment, as well as with dysexecutive syndrome.